From Ergonomic Design to Intelligent Healthcare: A Bibliometric Analysis of Elderly‑Oriented Research - Yusuf Nugroho Doyo Yekti; Ilma Mufidah; Dino Caesaron; Murman Dwi Prasetio (IJIES (International Journal of Innovation in Enterprise System), 2026)
The purpose of this study is to provide a bibliometric perspective on the research landscape of ergonomic equipment for the elderly, with particular attention to publication trends, collaboration networks, and thematic evolution. Publications indexed in the Scopus database between 2016 and 2026 were systematically identified and screened in accordance with the PRISMA framework. The analysis evaluates publication growth, leading journals and countries, citation performance, and emerging research themes. Bibliometrix (R package) and VOSviewer were employed to examine the intellectual structure of the literature and explore the evolution of its research themes. The results demonstrate sustained growth in publication activity throughout the study period, reflecting increasing attention to ergonomic approaches for supporting healthy aging. Applied Ergonomics is identified as the most productive journal in this area, while the United States and China remain the dominant contributors to research activity in the field. The thematic evolution analysis highlights a noticeable transition in research priorities, from early emphasis on elderly care, universal design, and ergonomic design to broader ergonomic-oriented studies, and more recently toward advanced technology-based applications, including artificial intelligence and virtual reality. The findings highlight the need for future studies to focus on innovative healthcare technologies for older adults, while ensuring that ergonomic and human-centered design considerations remain integral to their development. The insights presented in this study may assist scholars, policy stakeholders, and practitioners in navigating the evolving knowledge landscape while encouraging sustainable innovation for aging populations.